A rejoinder to Mr. Dobb's reply to Captain Middleton [electronic resource] : in which is expos'd, both his wilful and real ignorance of tides, &c. his Jesuitical prevarications, evasions, falsities, and false reasoning . in a word, an unparalelled disingenuity, and . a glaring impudence, are set in a fair light - Middleton, Christopher, d. 1770; Dobbs, Arthur, 1689-1765. (London : Printed for M. Cooper ., G. Brett ., and R. Amey ., 1745)
"What! Shall a Knitty, lousy Tar, My views expose, my Projects marr ." Electronic reproduction. Mode of access: Internet. 44